Odpowiedzi

2010-03-08T18:52:24+01:00
*5x-2=1
5x=2+1
5x=3/5
x=3/5
*3(y+1)=2y
3y+3=2y
3y-2y=-3
y=-3
*-x-1=-2x-2
-x+2x=1-2
x=-1
*5(-2+y)=7(-y+1)
-10+5y=-7y+7
5y+7y=10+7
12y=17/12
y=17/12
*2x(x-1)=2x2+4
2x²-2x=2x²+4
2x²-2x²-2x=4
-2x=4/(-2)
x=-2
1 5 1
  • Użytkownik Zadane
2010-03-08T18:53:09+01:00
A) 5x-2=1
5x=3
x=⅗

b)3(y+1)=2y
3y+3=2y
y=-3

c)-x-1=-2x-2
x=-1

d)5(-2+y)=7(-y+1)
-10+5y=-7y+7
12y=17
y=17/12
y=1 5/12

e) 2x(x-1)=2x2+4
2x²-2x=2x²+4
-2x=4
x=-2
2010-03-08T18:54:25+01:00
5x-2=1
5x=1+2
5x=3 /:5
x=3/5

3(y+1)=2y
3y+3=2y
3y-2y=3
y=3

-x-1=-2x-2
-x+2x=-2+1
x=-1

5(-2+y)=7(-y+1)
-10+5y=-7y+7
5y+7y=7+10
12y=17 /:12
y=17/12

2x(x-1)=2x2+4
2x(kwadrat)-2x=2x(kwadrat)+4 [x do kwadratu ci się skraca po obu stronach. zostaje ci więc]:
-2x=4 /:(-2)
x=-2

Mam nadzieję, że pomgłam.;) Pozdrawiam ;))

1 5 1